(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The study is performed with the major objective of gaining insights and knowledge about the role and importance of financial inclusion in the holistic development of a nation. The study also laid emphasis in finding the role of social capital as a moderator in the relationship between financial literacy and financial inclusion and impact of mobile banking as a moderator in the relationship between financial inclusion and development through mobile banking. Mediating role of Financial Inclusion was also explored in the study. The study is empirical in nature. The sample size of the study is 197 respondents which were chosen through non probabilistic convenient sampling method. The study uses structural equation modeling approach to find the association between financial literacy and financial inclusion and development. The study also performs hierarchical regression to check the moderation effect and Process Macro for mediation analysis. The research finds that there exists positive significant association between the level of penetration of the financial literacy and the extent of financial inclusion and between the prevailing level of financial inclusion and the level of nation’s development. It was also concluded from the study that mobile banking significantly act as a moderator for the relationship between financial literacy and financial inclusion and social capital was a significant moderator for the relationship between financial inclusion and development of the nation. Financial Inclusion partially mediates the relationship between financial literacy and development of the nation. Since the study is performed only on a sample of 197, belonging to Delhi NCR region, it can be taken as a limitation for the study.In future, the significance of demographic variables on the established relationship can be explored.